RANCANG BANGUN OWNCLOUD DAN MELINDUNGINYA TERHADAP SERANGAN DDOS - Molavi Arman; Inayatullah Inayatullah (Politeknik Negeri Batam, 2019)
Storage services using Google Drive or DropBox are used freely on the internet. Most of them use Cloud Computing technology. It means that the service on Cloud Computing could be provided quickly and it could minimize the interaction with provider. One of the constraints of data storage personally or professionally is the difficulty to access. There is also security disturbance from the network activity such as denial of service and virus infection. Difficulty to share data also becomes the main constraint to set the limit time of the document shared, with whom, and what access is allowed. These are some of the daily constraints and they disturb the flexibility especially in routine work. Therefore, firewall configuration is needed to minimize those disturbances so that the service could still be accessed.